Analisis Perbandingan Model Business Screening dan Financial Screening Indeks Saham Syariah Global berdasarkan Tinjauan Maqashid Syariah - R. Melda Maesarach; Siti Jamilah; Isfandayani; Muhammad Fahmi; Ali Amin, Irsyad (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2025)
This study aims to analyze the comparison between business screening and financial screening models used in global Islamic stock indices through the lens of maqashid shariah. The research employs an explanatory method based on literature review and expert interviews. The findings reveal that current screening models remain legal-formalistic and do not fully reflect the substantive values of maqashid shariah such as social justice, environmental protection, and business ethics. Therefore, a reformulation is needed to ensure the screening models fulfill not only legal compliance but also promote public benefit and prevent harm. This study recommends developing a maqashid-based screening framework that is more holistic and socially transformative.